Pengaruh Locus Of Control Dan Literasi Kewirausahaan Terhadap Perilaku Wirausaha Pada Wanita Wirausaha Kuliner Di Kecamatan Lima Kaum - Sari, Kumala; L V, Yuhendri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to examine the influence of locus of control and entrepreneurial literacy on the entrepreneurial behavior of women culinary entrepreneurs in Lima Kaum District. A causal-type quantitative research method was adopted, involving 105 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 30. The results indicate that both variables jointly have a significant effect, but only entrepreneurial literacy shows a positive and significant partial influence. These findings highlight the essential role of entrepreneurial literacy in shaping proactive and sustainable entrepreneurial behavior among women entrepreneurs.